The Effects of Mitral Valve Repair on Memory Performance, Executive Function, and Psychological Measures in Patients With Heart Failure. Issue 4 (May 2016) - Nikendei, Christoph; Schäfer, Hannah; Weisbrod, Matthias; Huber, Julia; Geis, Nicolas; Katus, Hugo A.; Bekeredjian, Raffi; Herzog, Wolfgang; Pleger, Sven T.; Schultz, Jobst-Hendrik
ABSTRACT: Objectives: Heart failure (HF) is a prevalent disease that remains costly and associated with a high mortality rate. HF is also associated with poor neurocognitive functioning. For the treatment for HF patients with severe mitral regurgitation, the MitraClip device has emerged as a promising interventional tool that reduces the mitral valve leakage and thus increases cardiac output. Currently, there is only limited knowledge on changes in cognitive and psychosocial functioning before and after the MitraClip intervention. Methods: Cognitive function (memory and executive function) and psychosocial measures (depression, anxiety, and quality of life) were assessed before and after the MitraClip intervention in 24 HF patients and 23 healthy participants (comparison group). Results: MitraClip intervention in HF patients was followed by improvements in figural long-term memory ( p = .003) and executive function (planning ability, p < .001) relative to the comparison group. In addition, the intervention resulted in a significant improvement in depression ( p = .002), anxiety ( p = .003) and quality of life scores (physical p = .017, mental p = .013) as well as improved 6-minute walk test results over time ( p = .002). Conclusions: The presented data provide evidence of a significant improvement in memory and executive function as well as in depression, anxiety, and quality of life scores in patients with chronic HF after MitraClip intervention. Further research is needed to shed light on the long-term development of cognitive function, psychosocial well-being, and clinical parameters after MitraClip intervention and how these factors depend on one another.